Cell biology and instrumentation : UV radiation, nitric oxide and cell death in plants - Blume, Yaroslav; Durzan, D. J.; Smertenko, Petro (NATO science series. Life and behavioural sciences, 2006)
Cellular processes, signaled by UV radiation, contribute to the behavior of plants under various stresses in the environment. This book aims to introduce developments and instrumentation for cell biology, to update our understanding of the effects of UV radiation, and to evaluate how plants use UV signals to protect against damage.